Digitalis therapy in patients with ventricular tachyarrhythmias - Schupp, Tobias; Müller, Julian; Zworowsky, Max von; Abumayyaleh, Mohammad S. A.; Weidner, Kathrin; Rusnak, Jonas; Mashayekhi, Kambis; Bertsch, Thomas; Akın, Ibrahim; Behnes, Michael (Scandinavian cardiovascular journal, 2022)
Objective. The study sought to assess the prognostic value of treatment with digitalis on long-term prognosis in patients with ventricular tachyarrhythmias and atrial fibrillation (AF) and/or heart failure (HF). Background. Data regarding the outcome of digitalis therapy following ventricular tachyarrhythmias is limited. Methods. A large retrospective registry was used including consecutive patients with episodes of ventricular tachycardia (VT) or fibrillation (VF) from 2002 to 2015. Patients treated with digitalis were compared to patients without. The primary prognostic endpoint was all-cause mortality at 3 years, secondary endpoints comprised a composite arrhythmic endpoint (i.e. recurrences of ventricular tachyarrhythmias, appropriate implantable cardioverter defibrillator (ICD) therapies, sudden cardiac death) and cardiac rehospitalization. Kaplan Mayer survival curves, multivariable cox regression, and time trend analyses were applied for statistics. Results. Eight hundred and thirty-one patients were included (20% treated with digitalis and 80% without). At 3 years, digitalis treatment was not associated with all-cause mortality following ventricular tachyarrhythmias (24 vs. 21%, log-rank p = .736; HR = 1.063; 95% CI 0.746-1.515; p = .736). However, digitalis therapy was associated with an increased risk of the composite arrhythmic endpoint (38 vs. 23%; log-rank p = .001; HR = 1.719; 95% CI 1.279-2.311; p = .001) and cardiac rehospitalization (31 vs. 18%; log-rank p = .001; HR = 1.829; 95% CI 1.318-2.538; p = .001), which was still evident within multivariable Cox regression analyses. Finally, digitoxin may be associated with a worse prognosis than digoxin. Conclusion. Digitalis therapy was not associated with mortality in patients with ventricular tachyarrhythmias, but with increased risk of the composite arrhythmic endpoint and cardiac rehospitalization at 3 years.